What’s it Like in There? Reflections on Being Educators in Military and Para-Military Settings in the UK and Canada - Jean Flynn; Beverley Morris (Adult Education Research Conference, 2007)
Drawing on the comparison of our work experiences within prisons and the British Army, we attempt to unpack and deepen our theoretical understandings of patriarchy, hegemony, power, and ‘other’.